Associations of eczema phenotypes with emotional and behavioural problems from birth until school age. The Generation R Study. (25th December 2019) - Hu, C.; Nijsten, T.; Pasmans, S.G.M.A.; de Jongste, J.C.; Jansen, P.W.; Duijts, L.
Summary: Background: Eczema phenotypes and emotional and behavioural problems are highly prevalent in childhood, but their mutual relationship is not fully clear. Objectives: To examine the associations of eczema phenotypes with school‐age emotional and behavioural problems, and the bidirectional associations of eczema and emotional and behavioural problems from birth until 10 years. Methods: This study among 5265 individuals was embedded in a prospective population‐based cohort study. Never, early transient, mid‐transient, late transient and persistent eczema phenotypes were identified based on parent‐reported, physician‐diagnosed eczema from age 6 months until 10 years. Emotional (internalizing) and behavioural (externalizing) problems were measured repeatedly using the Child Behavior Checklist from age 1·5 to 10 years. Cross‐lagged models were applied for bidirectional analyses. Results: All eczema phenotypes were associated with more internalizing problems and attention problems at age 10 years, compared with never having eczema: range of Z ‐score differences 0·14 [95% confidence interval (CI) 0·01–0·27] to 0·39 (95% CI 0·18–0·60). Children with early transient eczema had more aggressive behaviour symptoms at age 10 years ( Z = 0·16, 95% CI 0·05–0·27). Bidirectional analysis showed that eczema at 0–2 years was associated with more internalizing and externalizing problems at ages 3–6 and 10 years, while, inversely, only internalizing problems at 0–2 years were associated with an increased risk of eczema at age 10 years. Conclusions: Eczema phenotypes are very modestly associated with more somatic symptoms and attention problems at school age. Early transient eczema is associated with more aggressive behaviour symptoms. Directional effects seem to occur from early‐life eczema to later‐life internalizing and externalizing problems, rather than the reverse. Abstract : What's already known about this topic? Previous cohort studies using non‐data‐driven methods to define eczema phenotypes observed that children with early‐onset and persistent eczema had a higher risk of emotional and behavioural problems in preadolescence. Alternatively, previous cohort studies showed that children with emotional and behavioural problems had more severe eczema and eczema exacerbations in childhood. The direction of effects between eczema and emotional and behavioural problems is not fully clear. What does this study add? Taking the variability of eczema onset and persistence within and between children over time into account, all identified eczema phenotypes were very modestly associated with more somatic symptoms and attention problems at school age. Directional effects seem to occur from eczema leading to emotional and behavioural problems, rather than the reverse. Future research should focus on the effect of early optimal eczema management on mental health disorders in children later in life. Plain language summary available online